Routledge encyclopedia of narrative theory - Herman, David, 1962-; Jahn, Manfred, 1943-; Ryan, Marie-Laure, 1946- (Routledge, 2005)
The past several decades have seen an explosion of interest in narrative, with this multifaceted object of inquiry becoming a central concern in a wide range of disciplinary fields and research contexts. As accounts of what happened to particular people in particular circumstances and with specific consequences, stories have come to be viewed as a basic human strategy for coming to terms with time, process, and change.However, the very predominance of narrative as a focus of interest across multiple disciplines makes it imperative for scholars, teachers, and students to have access to a co- Resumé vydavatel
Keywords: naratologie; rétorika -- teorie; literární teorie; narratology; rhetoric -- theory; literary theory; elektronické knihy; encyklopedie; electronic books; encyclopedias